Plural Predication and Partitional Discourses - Beck, Sigrid (Proceedings of the Amsterdam Colloquium, 1999)
This paper argues against Schwarzschild's (1996) proposal that the interpretation of relational plural sentences is constrained by a contextually determined relation. Instead, I suggest that the data that seem to indicate the use of such relations are to be reanalysed as hidden universal quantification. This captures the fact that the only relations that seem to be available are equivalence relations. We come back to Krifka's (1989) proposal of a polyadic plural operator to handle cumulative readings of relational plurals and extend it to affect the situation/event argument of the relation.